SharePoint 2010 enterprise Search : IT pro training. (Microsoft, 2009)
"This Microsoft SharePoint Server 2010 Enterprise Search training course for IT Professionals provides a series of videos that demonstrate how to enable high-end enterprise search with SharePoint Server 2010 and Microsoft FAST Search Server 2010 for SharePoint. Learn about crawling and indexing content, and defining the user experience."--Resource description page.